Leaf Growth and Canopy Development of Three Sugarcane Genotypes under High Temperature Rainfed Conditions in Northeastern Mexico - Sergio Castro-Nava; Alfredo J. Huerta; José Manuel Plácido-de la Cruz; Epifanio Mireles-Rodríguez (International Journal of Agronomy)
The aim of this study was to compare sugarcane (Saccharum spp.) canopy developmental components of three commercial varieties (CP 72-2086, Mex 79-431, and Mex 68-P-23) in a subtropical environment under rainfed and high temperature conditions, a poorly described topic in the literature. A field experiment was carried out in southern Tamaulipas, Mexico, throughout November 2011–January 2013 crop cycle, during which 111 of the days had daily maximum temperatures at or above 35°C. Number of leaves, leaf area, leaf appearance rate, and leaf area index (LAI) were determined. Thermal time exposure, °Cd (°C day−1), was determined based on total number of green ligulate leaves using 10°C as the base temperature. At 5000°Cd the number of leaves per plant ranged from 32 to 40 and the dependence of leaf emergence rate as a function of temperature was confirmed. The leaf emergence rate of CP 72-2086 was significantly greater than that of the other two varieties. Cultivars did not differ with respect to leaf length but differed for all other parameters measured. These results show the potential importance of considering sugarcane varietal differences in leaf phenology and canopy development for breeding programs focusing on rainfed and high temperature conditions.